Prevalence and functional implications of Soleus and Tibialis anterior activation strategies during cycling - Jongerius, N.; Wainwright, B.; Wheat, J.; Bissas, A. (Journal of Sports Sciences, 2021)
Key areas of sports science research investigate the functional role of muscle activations within human movement. Even within relatively constrained movements like cycling, significant variability is observed in muscle activation strategies. Particular attention has been given to particular muscles, despite Soleus and Tibialis anterior muscles presenting a potentially functionally relevant split between monomodal and bimodal activation strategies. The current study (N = 54) investigated the prevalence and functional implications of these different strategies and identified, in addition to monomodal [Soleus: N = 24, Tibialis anterior: N = 7] and bimodal [Soleus: N = 12, Tibialis anterior: N = 31] strategies, a third group switching between strategies [Soleus: N = 16, Tibialis anterior: N = 13]. The combined Soleus group showed significantly higher Index of Force Effectiveness, lower negative work and lower radial forces than the bimodal group. Furthermore, bimodal Soleus strategies produced a period of significantly greater plantar flexion during the upstroke. No differences were found between the Tibialis anterior groups. These data show an identifiable group of cyclists utilising a combination of monomodal and bimodal strategies potentially benefiting mechanical effectiveness. Awareness of such functional implications can aid researchers and practitioners when interpreting cycling biomechanics data or intervention responses. Further research should investigate the factors that mediate transitions between activation strategies within the combined groups.